IMPLEMENTATION OF THE HEALTH LAW IN PROVIDING LEGAL PROTECTION FOR PATIENTS IN INDONESIA - Gunawan Widjaja; Dyah Ersita Yustanti (Adisam Publisher, 2025)
The implementation of the Health Law in Indonesia has the main objective of providing strong legal protection for patients, ensuring they receive proper and quality healthcare. The law outlines the rights of patients, such as transparent information on medical conditions, consent to medical treatment, and protection of medical privacy. In addition, the law also stipulates the responsibilities of medical personnel and health facilities to provide services in accordance with professional standards and codes of ethics. Nonetheless, the implementation of this law is faced with challenges such as lack of socialisation and limited resources in some areas. Therefore, cooperation from various parties is needed so that legal protection for patients in Indonesia can be realised effectively.